Coronavirus disease 2019 and the gut–lung axis - Dan Zhou (Elsevier, 2021)
ABSTRACT: Gastrointestinal and respiratory tract diseases often occur together. There are many overlapping pathologies, leading to the concept of the ‘gut–lung axis’ in which stimulation on one side triggers a response on the other side. This axis appears to be implicated in infections involving severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which has triggered the global coronavirus disease 2019 (COVID-19) pandemic, in which respiratory symptoms of fever, cough and dyspnoea often occur together with gastrointestinal symptoms such as nausea, vomiting, abdominal pain and diarrhoea. Besides the gut–lung axis, it should be noted that the gut participates in numerous axes which may affect lung function, and consequently the severity of COVID-19, through several pathways. This article focuses on the latest evidence and the mechanisms that drive the operation of the gut–lung axis, and discusses the interaction between the gut–lung axis and its possible involvement in COVID-19 from the perspective of microbiota, microbiota metabolites, microbial dysbiosis, common mucosal immunity and angiotensin-converting enzyme II, raising hypotheses and providing methods to guide future research on this new disease and its treatments.